(untitled) (The Review of Diabetic Studies, 2025)
Background: Prolonged hospital stays remain a significant concern in healthcare due to their association with increased morbidity, mortality, and elevated costs. Extended inpatient durations often result from a complex interaction between clinical complications, patient characteristics, and system inefficiencies. Understanding the underlying factors is critical for improving patient outcomes and optimizing hospital resource utilization. Objective: This systematic review aimed to synthesize empirical evidence on the complications and determinants that contribute to prolonged hospital stays, with a focus on medical, surgical, functional, and administrative factors influencing hospitalization duration. Methods: A systematic review methodology was conducted in accordance with PRISMA 2020 guidelines. Fifteen peer-reviewed studies published between 2006 and 2025 were analyzed. Eligible studies investigated adult inpatients and reported quantitative or qualitative findings on complications, risk factors, and outcomes associated with extended hospitalizations. Results: The review identified that postoperative complications, hospital-acquired infections, and functional decline among older adults are the most frequent causes of prolonged stays. Non-clinical contributors such as delayed discharge, emergency department bottlenecks, and administrative inefficiencies further exacerbate hospitalization length. Preventive measures, including early mobilization, infection control, and multidisciplinary care pathways, demonstrated effectiveness in reducing stay duration and improving recovery trajectories. Conclusion: Prolonged hospital stays are multifactorial in nature, arising from both patient-related and systemic causes. Implementing targeted preventive strategies, predictive models, and efficient discharge planning can significantly reduce hospitalization length, enhance care quality, and alleviate healthcare system burdens.